Hubungan Beban Kerja Dengan Kelengkapan Dokumentasi Asuhan Keperawatan Ruang Rawat Inap Rumah Sakit Bakti Timah Karimun Tahun 2023 - Apriliani Dwi Wahyuningsih; Sri Muharni; Utari Christya Wardhani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Old age is said to be the final stage of development in the human life cycle which experiences various health problems and is at high risk of dangerous diseases. Health problems that occur in the elderly in general are a decrease in organ function, changes in lifestyle, diet and physical activity which are often the main factors in degenerative diseases including hypertension which disrupts blood flow. This hypertension often occurs in the elderly where the blood pressure is at the upper limit ( Systole) is more than 140 mmHg and lower limit blood pressure (diastole) is more than 90 mmHg. One non-pharmacological treatment that can improve the flow of oxygen in the blood is laughter therapy. The aim of this research is to analyze the effect of laughter therapy using comedy videos on reducing blood pressure in elderly people with hypertension at the Tiban Baru Community Health Center, Batam City. The Batam City Health Service noted that hypertension occurs more frequently in elderly people aged 60-70 years and over with the highest number being 9,282 people at the Tiban Baru Community Health Center, Batam City. This research uses a quasi-experimental method with a pre-test and post-test design without control. The sample provided used the purpose sampling method with a total research sample of 20 respondents. Therefore, it can be concluded that there is an effect of laughter therapy on reducing blood pressure in elderly people with hypertension.